O PAPEL DO LIVRO DIDÁTICO DE GEOGRAFIA NO ÂMBITO DO PROGRAMA NACIONAL DO LIVRO DIDÁTICO (PNLD) NA REDE ESTADUAL DE ENSINO EM AQUIDAUANA, MS - ROGÉRIO REZENDE MEDEIROS (2024)
Studies regarding the textbook and its use have grown substantially in recent decades in Brazil, mainly due to the fact that it has assumed multiple aspects throughout its history, being at the same time a pedagogical, cultural and marketing element. Therefore, the present research aims to analyze the role of geography textbooks in the state education network in Aquidauana/MS, based on the National Textbook Program – PNLD. The methodological procedures adopted in this research are based on bibliographical, documentary and decree analysis, with subsequent recording of the information collected, in addition to fieldwork carried out with geography teachers from the seven state schools in the municipality of Aquidauana/MS. The National Textbook Program is the federal government's book distribution policy, being responsible for distributing textbooks to public schools across the country. It was characterized, over time, by the succession of decrees that brought major changes to the program, such as the distribution of CD ROM, dictionaries, multimedia materials and digital works and the expansion of benefiting groups. It was found that after the creation of the program, the country went through a period of numerous educational reforms that led to discussions about possible curricular standardization, which ended up becoming a reality recently with the implementation of the new National Common Curricular Base-BNCC. In the editorial field, despite the existence of a disputed territory, the presence of an editorial oligopoly reveals disparities in relation to smaller publishers. This fact can be perceived through the analysis carried out in the process of choosing the geography textbook, at PNLD 2024 in Aquidauana/MS, where the dominance of large publishers was verified. The time allocated to choosing the works is negligible given their importance in the school context. Even so, geography teachers in the Aquidauana state education network maintain a very close relationship with the textbook, and in many cases it is used as the main pedagogical resource in the classroom, guiding the teacher's planning.